Pendampingan dan Pengurusan Pembuatan Nomor Induk Berusaha (NIB) untuk UMKM Auliyabeauty.studio melalui OSS - Umi Nadifa Maulida; Armando Jihad Shabilal Mustaqim; Alyssa Nur Rahma Dwi; Adam Rafi Fatchurahman; Nafia Ilhama Qurratu’aini (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
SMEs (micro, small and medium enterprises) are very important for the Indonesian economy. However, many MSMEs do not understand the importance of having an NIB (Business Identification Number) as proof of the legality of their business. A similar thing also happened in Buduran Village, Sidoarjo. This community service program aims to provide MSME players with an understanding of how to register and obtain NIB. The activity begins with observing the situation, recording the perpetrators, as well as providing socialization and assistance. After participating in this activity, it is hoped that business actors will better understand and be able to manage their NIB. It is hoped that this program can continue to help more MSMEs in Sidoarjo Regency.